1997
DOI: 10.1007/s001010050419
|View full text |Cite
|
Sign up to set email alerts
|

Erhebungen zur kausalen perioperativen MortalitätVersuch einer deutschen „CEPOD-Studie”*,**

Abstract: In order to further reduce perioperative mortality in critically ill patients, every hospital should aim to optimize the structure of the surgical and anaesthesiological departments. A delay due to logistical or personnel problems may be a co-factor in perioperative mortality. Recovery rooms with experienced personnel should be the standard in postoperative anaesthesiological care. (ABSTRACT TRUNCATED)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
1
2
0
2
Order By: Relevance
“…Furthermore, Ethiopian studies have shown a POMR rate ranging between 3.4% and 4.6% (Davies et al 2016 ; Dugani et al 2017 ). Our findings concur with both the national and regional findings, in that the POMR is higher than that of HIC, but equivalent to the regional figures (Fichtner and Dick 1997 ). In LIC, 40% of the POMR is reported to be attributed to facility-based resource factors such as postoperative care infrastructure and cancer care pathway, while the rest is attributed to patient factors (GlobalSurg Collaborative and National Institute for Health Research Global Health Research Unit on Global Surgery 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, Ethiopian studies have shown a POMR rate ranging between 3.4% and 4.6% (Davies et al 2016 ; Dugani et al 2017 ). Our findings concur with both the national and regional findings, in that the POMR is higher than that of HIC, but equivalent to the regional figures (Fichtner and Dick 1997 ). In LIC, 40% of the POMR is reported to be attributed to facility-based resource factors such as postoperative care infrastructure and cancer care pathway, while the rest is attributed to patient factors (GlobalSurg Collaborative and National Institute for Health Research Global Health Research Unit on Global Surgery 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…Cardiac arrhythmias appear to be rather frequent in humans after surgery but are rarely life-threatening (Vicenzi 2000). Fichtner and Dick (1997) state that cardiac arrhythmias are primarily observed in human medicine during the phase after surgery. However, Hines and others (1992) describe nausea and vomiting as the most frequent complications after surgery, followed by disorders of the upper respiratory tract and hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy in the frequency of complications after surgery can be explained by the fact that different patients were grouped together. In the study by Fichtner and Dick (1997), nearly half of the patients were placed in a highrisk group due to their physical condition and surgery was frequently carried out on abdominal organs. There were also cases of accident and vascular surgery carried out under anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Leider gibt es keine aktuellen und repräsentativen Mortalitätsdaten aus Deutschland selbst. ¾ltere Untersuchungen in der geburtshilflichen Anästhesie [5] oder bei begrenzten Patientenkollektiven [6] legen jedoch nahe, dass der Anteil der Anästhesie als Todesursache in Deutschland nicht wesentlich anders sein dürfte als in anderen entwickelten Ländern.…”
Section: 1unclassified